Analysis of the Relationship Between Economic Growth, Energy Consumption, CO2, and Trade Openness: Indonesia - Muhammad Faruq; Muhammad Dandy Alif Wildana (Journal of Development Economic and Social Studies, 2025)
This study examines the causal relationship between energy consumption, carbon emission, trade openness, and economic growth and how the first three variables affects economic growth. Using data ranged from 1966 to 2023 from Indonesia, a vector error correction model and granger causality test is used to help analyze the data. Despite the expectations from exogenous growth theory and environmental Kuznets curve theory, the results reveal limited causality. Results shows that theres a causality from carbon emission towards economic growth and a bidirectional causality from energy consumption and economic growth with a long run effect from energy consumption, carbon emission, and trade openness towards economic growth. These findings suggest that that economic activities are reactive to environmental and energy trends. Policy implications include the need for integrated energy and environmental planning while recognizing the limited short-term impact of trade openness on economic growth dynamics in Indonesia.